STAG2 mutations in the normal colon induce upregulation of oncogenic pathways in neighbouring wildtype cells - Wei Ni Yew; Christopher James Dean; Dedrick Kok Hong Chan (PLoS ONE, 2025)
While driver mutations in the normal colon have been described, characterizing the role and function of these driver mutations in relation to colorectal oncogenesis remains incomplete. Here, we investigated the role of STAG2 mutants in the normal colon using patient-derived wildtype organoids. Using CRISPR-Cas9 gene editing, we generated STAG2 mutants, and co-cultured these mutants with wildtype organoids, mimicking the presence of such STAG2 mutants in the normal colon. We sought to determine the transcriptional impact of co-culture using scRNAseq. Surprisingly, we uncovered a possible cell-cell interaction between STAG2 mutants and wildtype organoids, in which wildtype organoids in co-culture with STAG2 mutants upregulated known oncogenic pathways. This included the upregulation of TNFα-signaling, as well as KRAS-signaling in wildtype organoids. These results suggested that STAG2 mutant cells exert a pro-oncogenic effect in a cell interactive manner, instead of via a cell autonomous approach. In conclusion, our findings demonstrate a novel mechanism of colorectal oncogenesis which can support further investigation.